(Auto)formação com musicais: “O descon(s/c)ertante flautista” e a peça didática “Diz que sim” de Bertolt Brecht - Noronha, José Renato (2017)
This thesis presented to Post-graduation Program (PPGE) of Center of Education (CE) of Federal University of Santa Maria (UFSM), in area of Education and Arts bring the importance of presence to (Self)formative process (JOSSO, 2010, 2010a; NÓVOA e FINGER 2010) did with musicals. Developed like a Formative (self)Research inspirited in Formative Research(JOSSO, 2010, 2010a) taked with a dispositive the experiment with Yes sayer (Der Jasager) a Learning Play of Bertolt Brecht (BENJAMIN, 1987 e 1987a; CONCÍLIO, 2016; KOUDELA, 2001; TEIXEIRA JÚNIOR, 2014; CALICO, 2008) inside the a Arts-based Educational Research (ABER).The A/R/Tograph method permits the author put himself in hybrid shape like: Artist, Researcher and Teacher (IRWIN e BELIDSON, 2010). The thesis says that presence in (Self)formation to music in scene do a kind of Experience, with capital letter, that incorporate not just a conceptual experience (Erfahrung) but the life experience (Erlebnis) (DEWEY, 1976 e 2010; TEIXEIRA e WESTBROOK, 2010; JOSSO, 2010; BENJAMIN, 1984,1987, 1987a, GUMBRECHT, 2010).This conception reaffirm the singularity of arts epistemology area. For a year and half, are did experiments where learning by presence was observed in creative process by Coletivo Baal from Florianópolis, Santa Catarina, Brazil in the a (Self) formative to musical-scene performance of spectacle Diz que sim (Yes sayer), and in the (Auto)Formative Musical: O Descon(s/c)ertante Flautista (Un-Concertive Piper). The presence marks and status built the process and in the work of art made suited of dates to reflexion presented (Darstellung) (BENJAMIN, 1984 e VASCONCELOS, 2013) with the dramaturgy based in The Pied Piper de Robert Browning (1841) also the dialogues scripted inside the thesis. The reseach contributes with the acknowledgement that kind of Experience when the presence learning is active by artistic practices, and also retake the music in Learning Plays experiments.